CARE FOR THE CHILD WITH A CHRONIC ILLNESS IN THE FAMILY HEALTH STRATEGY - Vanessa Medeiros da Nóbrega; Simone Soares Damasceno; Poliana Formiga Rodrigues; Altamira Pereira da Silva Reichert; Neusa Collet (Universidade Federal do Paraná, 2013)
The significant increase in children with chronic illnesses shows the importance of the qualification of the primary health care services and of the professionals who work there, so as to promote competencies in care, befitting these conditions' needs. This descriptive study, with a qualitative approach, aimed to analyze care for the child with a chronic illness in the Family Health Strategy. The interview, using a semi-structured script, was held care in the period between November 2008 to January 2009 with three mothers of children with chronic illnesses. The data was analyzed according to the principles of thematic analysis, and two issues emerged: Failure to resolve the health needs and Dissatisfaction with the attendance in the Family Health Strategy. The study showed the Strategy's fragility in meeting - with competency - the needs of the children with chronic illnesses, and the need for changes in the work process, such that integral care may be implemented